Identification of new HLA-A*0201-restricted cytotoxic T lymphocyte epitopes from LDHC in lung adenocarcinoma - Zhong, Ruifang; Guo, Xiaohong; Wu, Chuncai; Guo, Yangyi; Kang, Yanli; You, Jianbin; Chen, Falin; Chen, Qianshun; Chen, Liangyuan (Frontiers in Immunology, 2025)
BackgroundLactate dehydrogenase C (LDHC) is a kind of cancer-testis antigen (CTA) that has been reported to be a biomarker for diagnosis, efficacy evaluation, and recurrence monitoring of lung adenocarcinoma (LUAD). This study aims to assess the value of LDHC in peptide-based vaccines for LUAD immunotherapy.MethodsThe LDHC recombinant protein was purified and its effect on PC9 cells was evaluated by wound healing assay, Transwell invasion, and migration assay. Ten HLA-A2-restricted LDHC-derived peptides were predicted and synthesized, and the affinity for the HLA-A2 molecule was analyzed by T2 binding assay and molecule docking. Enzyme-linked immunospot (ELISpot) and LDH cytotoxicity assay were performed to determine the interferon-γ (IFN-γ) release level and tumor cell lysis ability of peptide-induced specific cytotoxic T lymphocytes (CTLs).ResultsThe LDHC recombinant protein promoted invasion and migration of PC9 cells. Three HLA-A2-restricted LDHC-derived peptides P2 (LDHC170–180, FRYLIGEKLGV), P5 (LDHC116–124, IMKSIIPAI), and P6 (LDHC172–180, YLIGEKLGV) had high affinity for the HLA-A2 molecule at 50 μg/mL. P6 (LDHC172–180, YLIGEKLGV) elicited the strongest IFN-γ-secreting cytotoxic T lymphocyte (CTL) response and exhibited potent cytotoxicity against HLA-A2-positive cells with high LDHC expression.ConclusionsLDHC may serve as a targetable biomarker for peptide-based immunotherapy of LUAD.